Learning in a Mixed Reality System in the Context of 'Industrie 4.0' - Guo, Qi [Verfasser] (My University, 2015)
"This contribution in the field of innovative approaches to training and education in technical subjects focuses on the potential of modern teaching and learning environments. The contribution is based on a theoretical introduction to Mixed Reality Systems and virtual teaching and learning systems, and as such provides an overview of current research regarding modern learning environments. In particular, it takes a close look at motivational effects in the context of web-based learning structures, human-object interactions, gamification and immersion. The article discusses both technical, user-relevant and pedagogical aspects as well as suggestions for further research in the context of Ausbildung 4.0." (Autorenreferat, BIBB-Doku)

"Der Beitrag fokussiert im Bezugsfeld innovativer Ansätze der Aus- und Weiterbildung in technischen Domänen die möglichen Potentiale von modernen Lehr- und Lernumgebungen. Aufbauend auf einer theoretischen Einführung zu Mixed Reality Systemen und virtuellen Lehr- und Lernsystemen liefert der Beitrag einen Überblick zum Forschungsstand zu modernen Lernumgebungen und geht hierbei insbesondere auf die motivationalen Effekte im Kontext webbasierter Lernstrukturen, Mensch-Objekt-Interaktionen, Gamification sowie Immersion ein. Im Beitrag werden sowohl technische, nutzerrelevante als auch pädagogische Aspekte diskutiert und Desiderate für eine weitergehende Forschung im Kontext einer Ausbildung 4.0 begründet." (Autorenreferat, BIBB-Doku)
Keywords: G 2.2.1 Technologisierung; L 4.2.3 Internetbasiertes Lernen / E-Learning; Industrie 4.0; Ausbildung; Lernplattform; E-Learning